2007
DOI: 10.1182/blood-2006-10-054924
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of elevated pretransplantation serum ferritin in patients undergoing myeloablative stem cell transplantation

Abstract: Iron overload could be a significant contributor to treatment-related mortality (TRM) for patients with hematologic malignancies undergoing hematopoietic stem cell transplantation (HSCT). We studied 590 patients who underwent myeloablative allogeneic HSCT at our institution, and on whom a pretransplantation serum ferritin was available. An elevated pretransplantation serum ferritin level was strongly associated with lower overall and disease-free survival. Subgroup multivariable analyses demonstrated that this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

27
288
5
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 397 publications
(326 citation statements)
references
References 19 publications
27
288
5
6
Order By: Relevance
“…Of these, only ferritin 41615 ng/ml (P ¼ 0.010, HR ¼ 2.74), older age (P ¼ 0.049, HR ¼ 1.63) and prior transplantation (P ¼ 0.002, HR ¼ 5.78) were adverse prognostic factors. The addition of albumin, a negative acute phase reactant, did not change the prognostic impact of 2 Causes of death in the low and high ferritin groups are given in Table 2.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, only ferritin 41615 ng/ml (P ¼ 0.010, HR ¼ 2.74), older age (P ¼ 0.049, HR ¼ 1.63) and prior transplantation (P ¼ 0.002, HR ¼ 5.78) were adverse prognostic factors. The addition of albumin, a negative acute phase reactant, did not change the prognostic impact of 2 Causes of death in the low and high ferritin groups are given in Table 2.…”
mentioning
confidence: 99%
“…Iron overload is a well-established adverse prognostic factor for allogeneic hematopoietic SCT in thalassemia, 1 and elevated pretransplant serum ferritin seems to adversely affect prognosis with myeloablative transplantation 2,3 for other diseases as well, primarily because of increased non-relapse mortality. We analyzed patients who underwent nonmyeloablative preparation for allogeneic transplantation to determine whether the presence of iron overload was also an adverse prognostic factor for patients undergoing nonmyeloablative transplants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Recent studies have demonstrated the prognostic impact of elevated serum ferritin on survival and complications following reduced-intensity SCT (RIST). [3][4][5][6] We previously reported a simple scoring system that consisted of serum ferritin and disease status at transplantation for predicting outcome in patients with AML and myelodysplastic syndrome (MDS).…”
mentioning
confidence: 99%
“…Iron overload, estimated by increased ferritin, appears to be associated with adverse outcomes and decreased survival. [1][2][3][4] There are several unanswered questions in this area. First, it is not clear how to best measure iron overload in these patients.…”
mentioning
confidence: 99%